Active site-directed tandem catalysis on CuO/VO-MnO2 for efficient and stable catalytic ozonation of S-VOCs under mild condition. (December 2020) - Yang, Jingling; Huang, Yajing; Chen, Yun-Wen; Xia, Dehua; Mou, Chung-Yuan; Hu, Lingling; Zeng, Jiawei; He, Chun; Wong, Po Keung; Zhu, Huai-Yong
Graphical abstract: Highlights: A tandem catalyst (CuO/VO -MnO2 ) for catalytic ozonation of S-VOCs has been developed. A significant improvement in CH3 SH elimination under mild condition over the state-of-the-art catalysts has been achieved. The superior catalytic performance of CuO/VO -MnO2 is attributed to the tandem adsorption and catalytic ozonation by multivalent CuO and oxygen vacancy rich MnO2 . The efficient electron replenishing interaction and cycling of oxygen vacancies at the reactive site of CuO/VO -MnO2 interface ensured the long-term stability. Abstract: Tandem catalysis can carry out the sequential coupling of multiple reactions in one operation, which is promising for sulfur-containing volatile organic compounds (S-VOCs) control. Herein, a tandem catalyst (CuO/VO -MnO2 ) consisting of well-dispersed CuO shell and oxygen vacancy-rich (VO ) hollow-structured MnO2 core exhibited superior adsorption and catalytic performance under the mild condition for the elimination of CH3 SH. The optimum 5CuO/VO -MnO2 can reach a significant improvement in CH3 SH elimination of ∼99 % conversion over bare CuO/ pristine MnO2 at 25 ℃ under a GHSV of 60, 000 mL h −1 g −1, and an almost 4-fold enhanced catalytic activity of the individual O3 with ∼99 % utilization of the applied O3 in the feed gas. The underlying tandem catalytic mechanism was in-depth identified by XPS, in situ DRIFTs and high-level computational study. The secret to the superior performance of CuO/VO -MnO2 lies in that CH3 SH was preferentially chemisorbed on multivalent CuO (Cu(I)/Cu(II)), then deeply oxidized into final product of SO4 2− /CO3 2− via the catalytic ozonation by multivalent CuO and oxygen vacancies of neighbouring VO -MnO2 . Attributed to the efficient electron replenishing interaction and cycling of active oxygen vacancies at the tandem reactive site of CuO/VO -MnO2 interface (Mn(IV) + Cu(II) + 2Olatt → Mn(II)/Mn(III) + VO + Cu(I) + O2 ), its lifetime can extend to 300 min with limited loss of activity. These findings thus open up a way to address current multiple challenges in S-VOCs control using a single hierarchical core-shell structure with tandem catalysis.